Mechanisms of enhanced cholesteryl ester transfer from high density lipoproteins to apolipoprotein B-containing lipoproteins during alimentary lipemia. - Tall, A (1986)
In vitro lipoprotein lipase enhances the cholesteryl ester transfer protein (CETP)-mediated transfer of cholesteryl esters from high density lipoproteins (HDL) to very low density lipoproteins as a result of lipolysis-induced alterations in lipoprotein lipids that lead to increased binding of CETP. To determine if there are similar changes during alimentary lipemia, we measured the transfer of cholesteryl esters from HDL to apo B-containing lipoproteins in incubated fasting and postprandial plasma. In seven normolipidemic subjects there was 2-3-fold stimulation of cholesteryl ester transfer in alimentary lipemic plasma. Cholesteryl ester transfer was stimulated when either the d less than 1.063-or d greater than 1.063-g/ml fraction of lipemic plasma was recombined with its complementary fraction of fasting plasma. To determine the distribution of CETP, plasma was fractionated by agarose chromatography and CETP activity was measured in column fractions in a standardized assay. In fasting plasma, most of the CETP was in smaller HDL, and a variable fraction was nonlipoprotein bound. During lipemia there was increased binding of CETP to larger phospholipid-enriched HDL and in two subjects an increase in CETP in apo B-containing lipoproteins. The total CETP activity of fractions of lipemic plasma was increased 1.1-1.7-fold compared with fasting plasma. Lipemic CETP activity was also increased when measured in lipoprotein-free fractions after dissociation of CETP from the lipoproteins. When purified CETP was incubated with phospholipid-enriched HDL isolated from alimentary lipemic or phospholipid vesicle-treated plasma, there was increased binding of CETP to the phospholipid-enriched HDL compared with fasting HDL, with a parallel stimulation in CETP activity. Thus, the pronounced stimulation of cholesteryl ester transfer during alimentary lipemia is due to (a) an increased mass of triglyceride-rich acceptor lipoproteins, (b) a redistribution of CETP, especially increased binding to larger phospholipid-enriched HDL, and (c) an increase in total activity of CETP, perhaps due to an increased CETP mass.